Meantone Temperaments on Lutes and Viols - Dolata, David (Book collections on Project MUSE., 2016)
Written for musicians by a musician, Meantone Temperaments on Lutes and Viols demystifies tuning systems by providing the basic information, historical context, and practical advice necessary to easily achieve more satisfying tuning results on fretted instruments. Despite the overwhelming organological evidence that many of the finest lutenists, vihuelists, and viola da gamba players in the Renaissance and Baroque eras tuned their instruments in one of the meantone temperaments, most modern early instrument players today still tune to equal temperament. In this handbook richly supplemented with figures, diagrams, and music examples, historical performers will discover why temperaments are necessary and how they work, descriptions of a variety of temperaments, and their application on fretted instruments. This technical book provides downloadable audio tracks and other tools for fretted instrument players to achieve more stable consonances, colorful dissonances, and harmonic progressions that vividly propel the music forward.